Islamic Educational Values in The Punggahan Tradition in Society - Budi Pangas Tuti; Imam Syafe’i; M. Sayyidul Abrori (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the Islamic educational values contained in the punggahan tradition and its contribution to the life of the community in Kaliasin Village, Tanjung Bintang District, South Lampung Regency. The punggahan tradition is a form of local wisdom practiced by Muslim communities in Indonesia, carried out before the arrival of Ramadan as an expression of gratitude and spiritual preparation. This research employs a qualitative approach with a descriptive research type. Data collection techniques include observation, in-depth interviews, and documentation involving religious leaders, community leaders, and local residents as informants. The data were analyzed through data reduction, data display, and conclusion drawing, with validity ensured through triangulation techniques. The findings reveal that the punggahan tradition in Kaliasin Village is implemented through several stages: grave visitation, religious gatherings and collective prayers, communal meals (kenduri), social interaction and mutual forgiveness, and environmental cleaning activities. Each of these stages reflects Islamic educational values, including aqidah (faith in Allah), ibadah (worship practices such as prayer, tahlil, and religious study), and akhlaq (moral values such as mutual forgiveness, cooperation, and togetherness). The contribution of Islamic educational values within the punggahan tradition is significant in shaping a religious, harmonious, and morally grounded society. This tradition serves not only as cultural heritage but also as an effective non-formal Islamic educational medium that instills spiritual, social, and moral values directly in community life.